2019
DOI: 10.1186/s12889-019-7677-1
|View full text |Cite
|
Sign up to set email alerts
|

Do nutrition and cash-based interventions and policies aimed at reducing stunting have an impact on economic development of low-and-middle-income countries? A systematic review

Abstract: BackgroundChildhood stunting is the most common manifestation of chronic malnutrition. A growing body of literature indicates that stunting can have negative repercussions on physical and cognitive development. There are increasing concerns that low- and middle-income countries (LMICs) are particularly susceptible to adverse consequences of stunting on economic development. The aim of this review is to synthesize current evidence on interventions and policies that have had success in reducing stunting and expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Nutrition education and counseling, immunization, water and sanitation hygiene programs were the components most frequently included in the intervention packages. Our study highlight similar ndings where coordination and collaborations are lacking due to political commitment, multi-sectoral collaboration between government, non-government, national, and international organizations exist and community service delivery platforms with active community engagement (Aguilera Vasquez & Daher, 2019). Existing stunting programs only focus on improving infants' nutritional status and then tend not to address the root causes of sensitive interventions.…”
Section: Discussionsupporting
confidence: 70%
“…Nutrition education and counseling, immunization, water and sanitation hygiene programs were the components most frequently included in the intervention packages. Our study highlight similar ndings where coordination and collaborations are lacking due to political commitment, multi-sectoral collaboration between government, non-government, national, and international organizations exist and community service delivery platforms with active community engagement (Aguilera Vasquez & Daher, 2019). Existing stunting programs only focus on improving infants' nutritional status and then tend not to address the root causes of sensitive interventions.…”
Section: Discussionsupporting
confidence: 70%
“…Global efforts to reduce stunting with an intersectoral approach demand greater attention to communication and articulation of objectives and methods within the different sectors involved in order to accomplish the nutritional goals (7). A recent systematic review showed that stunting was reduced by multisectoral efforts directed towards community-based nutrition with a strong emphasis on nutrition-sensitive and nutrition speci c programs (14). A recent systematic review by Aguilera and Daher collated macro-level policies and programs for stunting across government, health, and social assistance sectors of several countries including Peru, Malawi, Ethiopia, and Nigeria (14).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review showed that stunting was reduced by multisectoral efforts directed towards community-based nutrition with a strong emphasis on nutrition-sensitive and nutrition speci c programs (14). A recent systematic review by Aguilera and Daher collated macro-level policies and programs for stunting across government, health, and social assistance sectors of several countries including Peru, Malawi, Ethiopia, and Nigeria (14). Thus, other sectors such as agriculture, social assistance, health, education, water and sanitation, and the private sector have been identi ed with technical competencies to maximize nutrition results (7).…”
Section: Introductionmentioning
confidence: 99%
“…Global efforts to reduce stunting with an intersectoral approach demand greater attention to communication and articulation of objectives and methods within the different sectors involved in order to accomplish the nutritional goals [7]. A recent systematic review showed that stunting was reduced by multisectoral efforts directed towards community-based nutrition with a strong emphasis on nutrition-sensitive and nutrition specific programs [14]. A recent systematic review by Aguilera and Daher collated macro-level policies and programs for stunting across government, health, and social assistance sectors of several countries including Peru, Malawi, Ethiopia, and Nigeria [14].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review showed that stunting was reduced by multisectoral efforts directed towards community-based nutrition with a strong emphasis on nutrition-sensitive and nutrition specific programs [14]. A recent systematic review by Aguilera and Daher collated macro-level policies and programs for stunting across government, health, and social assistance sectors of several countries including Peru, Malawi, Ethiopia, and Nigeria [14]. Thus, other sectors such as agriculture, social assistance, health, education, water and sanitation, and the private sector have been identified with technical competencies to maximize nutrition results [7].…”
Section: Introductionmentioning
confidence: 99%